Acute worsening of glycemic control in a patient with type 2 diabetes and non‐small cell lung cancer after administration of lorlatinib. Issue 1 (20th January 2022) - Nakano, Yoshio; Miyasato‐Isoda, Mai; Gohma, Iwao; Fujisawa, Tomomi
Abstract: A patient with non‐small cell lung cancer (NSCLC) exhibited extreme hyperglycemia after lorlatinib treatment. The present case highlights the importance of glucose monitoring during lorlatinib administration and intensifying hyperglycemia treatment. Abstract : The present case indicated that 1) glucose monitoring is warranted during lorlatinib treatment and 2) the importance of intensifying hyperglycemia treatment after lorlatinib administration.